3D printing of sustainable concrete structures and characterisation - Chen, Xiaokang (2018)
With the rise of 3D printing in the Building and Construction industry, research in this industry have seen a substantial increase throughout the recent years where the first 3D printed house has made its mark in 2014. A hydration simulation based on the core-shrinking model was designed where the degree of hydration of Ordinary Portland Cement can be predicted with just the water-to-cement ratio as well as the curing temperature. An experimental set-up was developed where a concrete slab can be subjected to a constant temperature or a temperature gradient during the casting process. Through several experiments, a sustainable concrete mix is exposed to various constant temperatures and one temperature gradient for seven days. An increase of compressive strength is observed as the casting temperature increase. Additionally, the rate of strength gain reduces as the casting temperature increase. When subjected to a temperature gradient during casting, the compressive strength of the cement is similar to one that have been subjected to a constant temperature with the temperature being the average of the temperature gradient. There is an increase in the rate of temperature growth as the casting temperature increase, where the temperature of the concrete mix reaches its peak at a quicker rate. A preliminary investigation done on the heat flow of the concrete mix, however with the lack of information, the results produced are inconclusive and more investigation needs to be done.